Avaliação farmacológica do extrato hidroalcoólico das Flores de Pyrostegia venusta (Ker.) Miers - Veloso, Clarice De Carvalho (2010)
Pyrostegia venusta (Ker.) Miers (Bignoniaceae) is native to the Brazilian Cerrado and popularly known as “cipó-de-são-joão.” In traditional Brazilian medicine, the Pyrostegia venusta are used as a general tonic as well as a treatment for diarrhea, vitiligo, cough, and common diseases of the respiratory system related to infections, such as bronchitis, flu and cold. This study was conducted to evaluate the effects of a hydroethanolic extrac to flowers of Pyrostegia venusta (PvHE) on sickness behavior induced by lipopolysaccharide in mice, to evaluate the anti-inflammatory and analgesic properties of the PvHE and its phytochemical profile. To evaluate the effects of orally administered Pyrostegia venusta hydroethanolic extract on lipopolysaccharide-induced sickness behavior, mice were submitted to the forced swim test (FST) and the open field test. The PvHE was used to evaluate the anti-inflammatory and analgesic effects using carrageenan-induced paw oedema/ peritonitis and acetic acid-induced writhing/formalin-induced paw licking tests in Swiss albino mice respectively. Lipopolysaccharide (LPS,100μg/kg, i.p.) administration increased the time spent floating in the FST and depressed locomotor activity in the open field. Pretreatment with PvHE at test doses of 100 and 300 mg/kg,p.o. attenuated the behavioral changes induced by LPS in the FST and open field test. This effect was similar to pretreatment with dexamethasone (1mg/kg), which is a steroidal drug that inhibits immune and inflammatory responses, including cytokine production. The PvHE at test doses of 30-300 mg/kg p.o. clearly demonstrated anti-inflammatory effects by reduced paw edema induced by carrageenan and inhibited leukocyte recruitment into the peritoneal cavity. The extracts are tested in doses of 30-300 mg/kg, p.o. clearly demonstrated antinociceptive activity in acetic acid-induced writhing and formalin tests. The extract of Pyrostegia venusta attenuated the depressive-like and exploratory behaviors induced by lipopolysaccharide and demonstrated anti-inflammatory and antinociceptive action in mice and no apparent acute toxicity on oral administration. Thus, our results supported previous claims of the usefulness of these plants in traditional therapies and suggest that these plants may Pyrostegia venusta (Ker.) Miers (Bignoniaceae) is native to the Brazilian Cerrado and popularly known as “cipó-de-são-joão.” In traditional Brazilian medicine, the Pyrostegia venusta are used as a general tonic as well as a treatment for diarrhea, vitiligo, cough, and common diseases of the respiratory system related to infections, such as bronchitis, flu and cold. This study was conducted to evaluate the effects of a hydroethanolic extrac to flowers of Pyrostegia venusta (PvHE) on sickness behavior induced by lipopolysaccharide in mice, to evaluate the anti-inflammatory and analgesic properties of the PvHE and its phytochemical profile. To evaluate the effects of orally administered Pyrostegia venusta hydroethanolic extract on lipopolysaccharide-induced sickness behavior, mice were submitted to the forced swim test (FST) and the open field test. The PvHE was used to evaluate the anti-inflammatory and analgesic effects using carrageenan-induced paw oedema/ peritonitis and acetic acid-induced writhing/formalin-induced paw licking tests in Swiss albino mice respectively. Lipopolysaccharide (LPS,100μg/kg, i.p.) administration increased the time spent floating in the FST and depressed locomotor activity in the open field. Pretreatment with PvHE at test doses of 100 and 300 mg/kg,p.o. attenuated the behavioral changes induced by LPS in the FST and open field test. This effect was similar to pretreatment with dexamethasone (1mg/kg), which is a steroidal drug that inhibits immune and inflammatory responses, including cytokine production. The PvHE at test doses of 30-300 mg/kg p.o. clearly demonstrated anti-inflammatory effects by reduced paw edema induced by carrageenan and inhibited leukocyte recruitment into the peritoneal cavity. The extracts are tested in doses of 30-300 mg/kg, p.o. clearly demonstrated antinociceptive activity in acetic acid-induced writhing and formalin tests. The extract of Pyrostegia venusta attenuated the depressive-like and exploratory behaviors induced by lipopolysaccharide and demonstrated anti-inflammatory and antinociceptive action in mice and no apparent acute toxicity on oral administration. Thus, our results supported previous claims of the usefulness of these plants in traditional therapies and suggest that these plants may be useful in the treatment of disorders that induced sickness behavior, such as flu and cold.